E-023 Endovascular treatment of peripheral cerebellar aneurysms: parent vessel occlusion and ischemic complications. (22nd July 2018) - Yoo, D; Cho, Y; Kang, H; Cho, W; Kim, J; Han, M
Abstract : Background and purposes: Peripheral cerebellar artery aneurysms are rare, accounting less than 1% of the intracranial aneurysms. Parent vessel occlusion (PVO) is required on occasion to achieve complete occlusion of the lesion. PVO, however, harbors the potential risk of ischemic complication in two ways; first, brainstem and cranial nerve ischemia due to obliteration of perforator from proximal segments, and second, cerebellar ischemia by occlusion of distal segments. In this study, we describe a retrospective series of 23 patients with peripheral cerebellar artery aneurysms treated by endovascular approach. We also reviewed previous literatures to compare first, the outcome between selective occlusion and PVO, and second, complication after PVO of proximal segments and distal segments. Methods: Fifteen and eight aneurysms were located at proximal and distal segment of the parent artery, respectively. PVO was performed in 15 patients and selective occlusion in 8 patients. For further evaluation of outcome with large numbers, literature search for endovascularly treated peripheral cerebellar artery aneurysms was done. Outcomes were compared between PVO and selective occlusion group. Incidence of ischemic complication after PVO at brain stem and cerebellum was assessed. Results: Angiographic total occlusion was achieved in 19 (83%) aneurysms with no case of rebleeding. After PVO, infarction was present in eight cases, of which two were symptomatic. Based on literature review (167 aneurysms), PVO produced higher total occlusion rate and lower recanalization rate. Rebleeding occurred in only one cases in PVO group, and none in selective occlusion group. After PVO at proximal segment, three (6.0%) symptomatic infarction occurred in cerebellar and two (4.0%) in brain stem. After PVO at distal segment, there were five symptomatic cerebellar infarctions (9.1%). Conclusions: Endovascular treatment is safe and durable option in managing peripheral cerebellar artery aneurysm. PVO offers more effective occlusion of the lesion compared to selective occlusion, though both modality were excellent in preventing rebleeding. PVO may be complicated with ischemic event and PVO at proximal segments carries low but not negligible risk of brain stem infarction. Disclosures: D. Yoo: None. Y. Cho: None. H. Kang: None. W. Cho: None. J. Kim: None. M. Han: None.